2021
DOI: 10.1158/0008-5472.can-21-0993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ERK5 Elicits Cellular Senescence in Melanoma via the Cyclin-Dependent Kinase Inhibitor p21

Abstract: Melanoma is the deadliest skin cancer with a very poor prognosis in advanced stages. Although targeted and immune therapies have improved survival, not all patients benefit from these treatments. The mitogen-activated protein kinase ERK5 supports the growth of melanoma cells in vitro and in vivo. However, ERK5 inhibition results in cell-cycle arrest rather than appreciable apoptosis. To clarify the role of ERK5 in melanoma growth, we performed transcriptomic analyses following ERK5 knockdown in melanoma cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…However, recent findings showed that, in melanoma samples, mutated BRAF positively regulates activation of ERK5 that was highly correlated with melanoma proliferation by in vitro and in vivo studies [ 87 ]. Lately, Tubita et al [ 88 ] observed a blockade in the cell cycle progression in ERK5 knockdown in BRAF-mutated melanoma cells linked to the activation of cellular senescence mechanisms which includes the involvement of CDK inhibitors. Additionally, NRAS -mutant melanoma cells showed a proliferative advantage when, in response to MEK inhibitors treatment, expressed high levels of active ERK5 and the high rate of ERK5 was correlated with nuclear localization of the stem-like factor KLF2 [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent findings showed that, in melanoma samples, mutated BRAF positively regulates activation of ERK5 that was highly correlated with melanoma proliferation by in vitro and in vivo studies [ 87 ]. Lately, Tubita et al [ 88 ] observed a blockade in the cell cycle progression in ERK5 knockdown in BRAF-mutated melanoma cells linked to the activation of cellular senescence mechanisms which includes the involvement of CDK inhibitors. Additionally, NRAS -mutant melanoma cells showed a proliferative advantage when, in response to MEK inhibitors treatment, expressed high levels of active ERK5 and the high rate of ERK5 was correlated with nuclear localization of the stem-like factor KLF2 [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous flow cytometry results have shown that icaritin causes cellular S-phase arrest. The cell cycle regulates cell differentiation and proliferation and is also closely related to cellular senescence (Shi et al, 2021;Tubita et al, 2022). The induction of cellular senescence is one of the mechanisms of anti-tumor drugs.…”
Section: Icaritin Induces Hone1 and Hne1 Cell Senescencementioning
confidence: 99%
“…Another potential pathway of interest to combat intrinsic or acquired resistance to immunotherapy and BRAF/MEK1/2 inhibitors is the MEK/ERK5 pathway (Figure 2). Genetic and pharmacological inhibition of ERK5 in melanoma cells leads to irreversible cellular senescence mediated by p21 and suppresses resistance to BRAF and MEK1/2 inhibition in vitro [62,63]. In TNBC, targeting ERK5 inhibits cell cycle progression, promotes apoptosis, and enhances tumor cell sensitivity to chemotherapy [64].…”
Section: Novel Pharmacological Inhibitors Of Pi3k and Mapk Pathwaysmentioning
confidence: 99%